Periodontal evaluation of pregnant women after delivery: a cross sectional study - Renata Torres, Claudia; Ferreira Novo, Neil; Dias Bertagnon, José Ricardo; Colombo-Souza, Patrícia; Tiemi Shio, Marina; França, Carolina Nunes França (Journal of Health Care, 2021)
Introduction: The association between periodontal status and adverse pregnancy outcomes has been studied since 1990 with conflicting results. Premature birth and low birth weight babies were the two main concerns addressed by the investigations, related to periodontal disease. Objectives: The present study investigated the prevalence of periodontal disease in women in the postpartum period seen at a public hospital in the southern region of the city of São Paulo and the assessment of a possible relationship between periodontal disease and the frequency of prematurity and low birth weight. Casuistry and Methods: This is a cross-sectional study that selected pregnant women attended for delivery in a public hospital, and verified the possible association between periodontal disease and the number of preterm births and low birth weight babies. The periodontal examination, including bleeding on probing and plaque index, was performed within 48 hours after delivery by the same examiner on all teeth at six locations per tooth using a Marquis periodontal probe. The data were analyzed using the Kruskal-Wallis and chi-square tests, at the level of statistical significanceÎ± = 0.05. Results: During the study period, 109 mothers were examined, 13 of whom had babies weighing less than 2,500 g, 8 of whom were less than 37 weeks pregnant; among those of normal weight, there were another 6 newborns, totaling 14 babies with shorter gestation times. Only 7 mothers had periodontal health, with gingivitis and periodontitis predominating, respectively, in 50 and 52 mothers. There was no association with mean age, number of prenatal visits, gestational age, weight and length of the baby. There was also no association with health history data, especially diabetes, hypertension and smoking. Conclusions: The incidence of prematurity and low birth weight was considered low and was not associated with maternal periodontal status.
Keywords: gingivitis; periodontitis; premature; low birth weight.